Mineral analyses and whole rock major element, trace element and Sr-, Nd- Pb-isotope data of plutonic rocks from Maronia and Kassiteres, NE Greece - Schaarschmidt, Anna; Klemd, Reiner; Voudouris, Panagiotis C; Melfos, Vasilios; Haase, Karsten M (PANGAEA, 2020)
The dataset contains mineral analyses as well as whole rock analyses of plutonic rocks from the Oligocene Maronia and Kassiteres plutons in NE Greece. Major and trace elements were measured using X-ray fluorescence spectrometry and quadrupole inductively coupled plasma mass spectrometry, respectively. Sr and Nd isotopes were measured using thermal ionization multi-collector mass spectrometry. Pb isotopes were measured using multi-collector mass spectrometry. Feldspar, pyroxene, amphibole, biotite, apatite, magnetite and ilmenite were analyzed using an electron microprobe. All analyses were carried out at the GeoZentrum, Friedrich-Alexander-Universität in Erlangen. The dataset gives detailed insight into the genesis of shoshonitic and calc-alkaline arc magmas and its connection to porphyry-type mineralization.
Keywords: isotope data; mineral data; trace elements